Whole genome sequencing of apparently mutation-negative MEN1 patients. Issue 1 (January 2020) - Backman, Samuel; Bajic, Duska; Crona, Joakim; Hellman, Per; Skogseid, Britt; Stålberg, Peter
Abstract : Objective: Multiple endocrine neoplasia type 1 (MEN1) is an autosomal dominant syndrome usually caused by loss-of-function mutations in the MEN1 gene. However, a minority of patients who fulfill the criteria for MEN1 are not found to harbor MEN1 mutations. Besides, some of these individuals, present with a subtly different phenotype suggestive of sporadic disease. The aim of the present study was to investigate the genetic architecture of mutation-negative MEN1. Design: Fourteen patients with a clinical diagnosis ( n  = 13) or suspicion ( n  = 1) of MEN1 who had negative genetic screening of the MEN1 gene were included. Methods: Constitutional DNA from the included patients, as well as tumor DNA from six of the patients, was subjected to whole genome sequencing. Constitutional variants were filtered against population databases and somatic variants were studied under a tumor-suppressor model. Results: Three patients carried pathogenic variants (two splice-site variants, one missense variant) in MEN1 that had not been detected during routine clinical sequencing, one patient carried a pathogenic variant in CASR and one patient carried a gross deletion on chromosome 1q which included the CDC73 gene. Analysis of matched tumor DNA from six patients without mutations did not detect any recurrent genes fulfilling Knudson's two-hit model. Conclusion: These results highlight the possibility of germline mutations being missed in routine screening, the importance of considering phenocopies in atypical or mutation-negative cases. The absence of apparent disease-causing mutations suggests that a fraction of MEN1 mutation-negative MEN1 cases may be due to the chance occurrence of several endocrine tumors in one patient.